Study of the utbbbe soi tunnel-fet working as a dual-technology transistor - Mori, Carlos A. B.; Agopian, Paula G. D. [UNESP]; Martino, João A. (Journal of Integrated Circuits and Systems, 2021)
— In this work we further investigate the operation of theBESOI (Back-Enhanced Silicon-On Insulator) Dual-Technology FET, analyzing not only its behavior as a p-type Tunnel-FET when a negative back bias is applied to the struc-ture, but also as an nMOS when a positive back bias is applied. The working principle is based on the generation of a channel of either holes or electrons by the back gate electric field, which can then be depleted through the front gate bias. TCAD device simulation was used for the proof of concept.
Keywords: Dual technology transistor; MOSFET; Reconfigurable transistor; Silicon-On-Insulator (SOI); Tunnel-FET